PUB601 : Self-publishing and entrepreneurship / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (Universiti Teknologi MARA (UiTM), 2018)
Today, fewer publishing companies are taking on new authors and self-publishing is becoming a very viable and profitable option. In this course, students will learn how to format their manuscript for the printers; copyright, disclaimers and get their ISBN number; and, most importantly, how to market their book and sell it. This course takes them through the complete process of turning their dream of becoming a published author into reality.